2005
DOI: 10.1007/s10532-004-2057-6
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic biodegradation of vegetable oil and its metabolic intermediates in oil-enriched freshwater sediments

Abstract: Anaerobic biodegradation of vegetable oil in freshwater sediments is strongly inhibited by high concentrations of oil, but the presence of ferric hydroxide relieves the inhibition. The effect of ferric hydroxide is not due to physical or chemical interactions with long-chain fatty acids (LCFAs) that are produced as intermediates during metabolism of vegetable-oil triglycerides. The anaerobic biodegradation of canola oil and mixtures of acetic and oleic acids, two important intermediates of vegetable-oil metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
(55 reference statements)
0
22
0
Order By: Relevance
“…Although it is biodegradable, anaerobic metabolism of vegetable oil may produce intermediates that are inhibitory to aceticlastic methanogens and hydrogen-producing acetogens (Hanaki et al, 1981;Koster and Cramer, 1987;Hwu et al, 1996;Lalman and Bagley, 2001). Such inhibition was observed during anaerobic degradation of vegetable oil in freshwater sediments (Li et al, 2001(Li et al, , 2005. Vegetable oils and animal fats have been reported to be phytotoxic (Forster, 1992;Sampedro et al, 2005) and to exert other toxic effects on fish (Pustowka et al, 2000) in aquatic ecosystems.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Although it is biodegradable, anaerobic metabolism of vegetable oil may produce intermediates that are inhibitory to aceticlastic methanogens and hydrogen-producing acetogens (Hanaki et al, 1981;Koster and Cramer, 1987;Hwu et al, 1996;Lalman and Bagley, 2001). Such inhibition was observed during anaerobic degradation of vegetable oil in freshwater sediments (Li et al, 2001(Li et al, , 2005. Vegetable oils and animal fats have been reported to be phytotoxic (Forster, 1992;Sampedro et al, 2005) and to exert other toxic effects on fish (Pustowka et al, 2000) in aquatic ecosystems.…”
Section: Resultsmentioning
confidence: 98%
“…It has already been shown that floating vegetable oil spills can be effectively removed from surface waters by sedimentation with clay minerals (Wincele et al, 2004), and the oil can be efficiently mineralized under anaerobic conditions in freshwater sediments (Li et al, 2001(Li et al, , 2005Li and Wrenn, 2004). The objective of this study was to evaluate the toxicity of sediments contaminated by the concentrations of vegetable oil that can be produced by sedimentation of floating vegetable oil spills by clay and other dense minerals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, the anaerobic biodegradation of vegetable oil in sediments began (Li et al 2001(Li et al , 2005Li and Wrenn 2004), explaining the drop in oil concentration in sediments over time (see Table 1). Although clay can effectively transfer vegetable oil from the water to sediments where anaerobic degradation of vegetable oil can occur, the metabolic intermediates of degradation may be toxic to microorganisms (Cherrington et al 1991), mussels (Mudge 1995) and amphipods (Li et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In freshwater sediments, however, the addition of calcium chloride and clay reduced the rate of methanogenesis from canola oil, whereas the addition of ferric hydroxide stimulated the rate of its conversion to methane ( Li and Wrenn, 2004 ). Furthermore, enrichment of freshwater sediments by growth on vegetable oil in the presence of ferric hydroxide stimulated the rate of methanogenesis from vegetable oil relative to sediments that were enriched in its absence ( Li et al, 2005 ). Unlike calcium and clay, ferric hydroxide can also serve as an alternative electron acceptor in the anaerobic degradation of lipids and long‐chain fatty acids (Figure 1).…”
Section: Introductionmentioning
confidence: 99%